1996
DOI: 10.1007/bf02088743
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of mucin in whole-gut lavage fluid obtained from patients with inflammatory bowel disease

Abstract: Whole-gut lavage fluid, collected by administering an electrolyte lavage solution orally, was found to be an excellent and easily collectable source of abundant mucin. Furthermore, the biochemical features of the mucin from patients with ulcerative colitis and Crohn's disease were investigated. The mucin was separated into four fractions by Sepharose CL-4B, Sepharose CL-2B, and DEAE Sephacel chromatography. Compared with healthy subjects, the total yields of mucin from ulcerative colitis patients were low due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Concerning human absorption, Al is poorly absorbed but many luminal compounds influence bioavailability determined by its solubility and diffusibility. One such factor is intestinal mucin, which is altered in CD patients 27,72 . Al is absorbed along the gastrointestinal tract, which is the target organ for CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning human absorption, Al is poorly absorbed but many luminal compounds influence bioavailability determined by its solubility and diffusibility. One such factor is intestinal mucin, which is altered in CD patients 27,72 . Al is absorbed along the gastrointestinal tract, which is the target organ for CD.…”
Section: Discussionmentioning
confidence: 99%
“…One such factor is intestinal mucin, which is altered in CD patients. 27,72 Al is absorbed along the gastrointestinal tract, which is the target organ for CD. In fact, once absorbed, it is transported by transferrin at the sites left vacant by iron.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the thickness of the adherent mucus layer was reduced in UC compared with the normal rectum but in contrast, the thickness of the mucus layer in the rectum was increased in CD (20). These results were mirrored by the yields of mucin obtained from whole‐gut lavage, which were low in UC but high in CD (22). Recently, using preservation of mucus in Carnoy’s solution Swidsinski et al.…”
Section: Introductionmentioning
confidence: 88%
“…In severe UC the mucus layer and goblet cell density were significantly reduced and likely to contribute to the symptomatology of the disease. of mucin obtained from whole-gut lavage, which were low in UC but high in CD (22). Recently, using preservation of mucus in Carnoy's solution Swidsinski et al also demonstrated a reduction in the mucus layer in UC (23).…”
Section: What's Newmentioning
confidence: 99%
“…Although this result is very interesting, it can be thought to reflect goblet cell depletion and recovery. Saitoh et al 8 reported the measurement of mucin in whole gut lavage fluid from patients with inflammatory bowel disease. It is doubtful whether the recovery of mucin in the lavage fluid is perfect, and it is uncertain whether the origin of the mucin is from the inflammatory or the normal mucosa.…”
Section: Introductionmentioning
confidence: 99%